2018
DOI: 10.1177/0886260518805100
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Factors Associated With Child Abuse Perpetration: A Nationwide Population-Based Retrospective Study

Abstract: Differences in child abuse perpetration between individuals with and without mental disorders remain obscure. This study compared the risk difference and further investigated the association between the category of mental disorders and child abuse perpetration. A total of 681,970 adults from the 2002 to 2013 Taiwan National Health Insurance Research Database were analyzed, including 340,985 patients with psychiatric disorders (International Classification of Diseases, Ninth Revision, Clinical Modification [ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…The finding that caregiver vulnerabilities varied across types of substantiated maltreatment is consistent with other research suggesting an association between specific caregiver risk factors and the perpetration of specific types of CM (Chaffin et al, 1996; Chang et al, 2021; Pittman & Lee, 2004; Westad & McConnell, 2012). Findings from this study are also consistent with research suggesting that the presence of caregiver vulnerabilities may be most pronounced in homes with more than one type of CM (Hartley, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding that caregiver vulnerabilities varied across types of substantiated maltreatment is consistent with other research suggesting an association between specific caregiver risk factors and the perpetration of specific types of CM (Chaffin et al, 1996; Chang et al, 2021; Pittman & Lee, 2004; Westad & McConnell, 2012). Findings from this study are also consistent with research suggesting that the presence of caregiver vulnerabilities may be most pronounced in homes with more than one type of CM (Hartley, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Substance abuse (Chaffin et al, 1996; Chang et al, 2021; Dakil et al, 2012; Dube et al, 2001; Steenrod & Mirick, 2017; Walsh et al, 2003; Whitaker et al, 2008), cognitive/intellectual impairments (McConnell et al, 2011a, 2011b; Slayter & Jensen, 2019), mental health issues (Chaffin et al, 1996; Chang et al, 2021; MacMillan et al, 2013; Walsh et al, 2002; Whitaker et al, 2008), physical health problems (Chang et al, 2021; McGaw et al, 2010), concurrent intimate partner violence (IPV; Casanueva et al, 2009; Dakil et al, 2012; McGaw et al, 2010; McGuigan & Pratt, 2001), caregiver young age (Chang et al, 2021; Hovdestad et al, 2015), and a personal history of child abuse or neglect (McGaw et al, 2010; Whitaker et al, 2008) have all been identified as risk factors for the perpetration of CM. Many of these same perpetrator vulnerabilities have also been shown to be associated with child functional impairments (Westad & McConnell, 2012), re-reports to child protective services (Casanueva et al, 2009; Connell et al, 2007; De Panfilis & Zuravin, 2002; Jonson-Reid et al, 2010), and increased likelihood that the case will be substantiated (vs. unsubstantiated) within the child welfare system (Dakil et al, 2012; McConnell et al, 2011b; Slayter & Jensen, 2019; Trocmé et al, 2009; Wekerle et al, 2007).…”
mentioning
confidence: 99%
“…Child maltreatment is associated with disorganized attachment and adverse outcomes ( Cyr et al, 2010 ). The prevalence of child maltreatment is elevated in the presence of a parental mental disorder, even more so when both parents are affected ( Chang et al, 2018 ). In a review regarding the impact of traumatic stress from birth to age 5, Chu and Lieberman (2010) argued that the prevalence of trauma in early childhood is highly underestimated and seldom investigated by researchers.…”
Section: Resultsmentioning
confidence: 99%
“…The Latin American and Caribbean study, which included 26 countries and analyzed 55248 adolescents aged 13-15 years, estimated that for Honduras 16% had alcohol use: one of the lowest percentages in the region (22). In Taiwan, a total of 681970 adults from the National Health Insurance Research Database from 2002-2013 were analyzed, nding that substance use disorders were signi cantly associated with higher odds of child abuse perpetration, especially physical abuse (23). Our data show low alcohol consumption in adolescents, but a high level of intrafamily violence, in addition, national data show female predominance.…”
Section: Discussionmentioning
confidence: 99%